A Meta-Analysis on Mobile-Assisted Language Learning Applications: Benefits and Risks. Issue 1 (16th September 2022) - Mihaylova, Mariela; Gorin, Simon; Reber, Thomas P.; Rothen, Nicolas
Mobile language learning applications are a pervasive facet of modern life, however evidence on their effectiveness on L2 learning outcomes is lacking. In the current work, we sought to determine the effect of mobile language learning applications on L2 proficiency between groups who used mobile language learning applications and control groups who learned with traditional methods on L2 achievement. We systematically searched journal articles and grey literature between 2007–2019 and performed a quantitative meta-analysis based on 23 synthesized effect sizes. We also performed risk of bias and quality of evidence assessments on our included papers. We found a moderate-to-strong overall effect ( g = 0.88) of learning achievement using mobile language applications compared to control groups who learned with traditional approaches. At the same time, we found high risk of bias and low quality of evidence across all included studies. Our results provide evidence for mobile applications as a beneficial tool for second language learning. However, findings should be treated with caution due to risks of high bias and low quality of evidence. Improvements for future studies are discussed.